Applying Game Theory to Teach the PERT Scheduling Method - Eric Forcael; Carla Contreras; Caroll Francesconi; Felipe Baesler (Applied Sciences)
This research focuses on applying Game Theory to teach the PERT scheduling method to civil engineering students. The work was carried out with students from the Construction Planning and Scheduling course, who were given face-to-face classes on Game Theory applied to teaching the PERT method. This proposal considers that gamification plays a role in user engagement, while Game Theory contributes to data analysis and decision strategies. It began with an initial pre-test evaluation consisting of questions classified by items and evaluation criteria to teach the PERT method using Game Theory, followed by a post-test and a quantitative evaluation that allowed to know the perception and interests of the students. Using Game Theory principles in teaching the PERT method demonstrated improvements in students. In addition, the results presented statistically significant differences in favor of using Game Theory, which would allow it to be proposed as a viable option for teaching PERT and other scheduling methods.